Grapevine genetics after the genome sequence: Challenges and limitations - Martínez Zapater, José M. (2010)
The publication of the genome sequences of inbred grapevine plant PN40024 and the cultivar Pinot Noir has provided a new generation of molecular tools and has opened the way to functional genomics in grapevine. Establishing gene biological function is now a major challenge requiring the parallel development of molecular and genetic information. New massive pyrosequencing technologies will ensure no shortage of nucleotide sequence information. However, genetic analysis and genetic tools in grapevine still require additional development. Exploiting the existing natural genetic variation in Vitis vinifera L. and other inter-fertile Vitis species should be a priority to focus functional analyses on genes contributing to phenotypic variation because their genetic variation constitutes the basis for genetic improvement of classical cultivars and for the development of new ones. In this review, we discussed the current molecular and genetic tools available in grapevine and considered those that need to be developed to exploit natural genetic variation in the analyses of gene function. We also reviewed the scarce information on the genetic and molecular structure of relevant grapevine traits and proposed future directions.